Отпущение грехов: роман / Фрида Митчелл - Митчелл Фреда (Пламя страстей, 2002)
Экземпляры: ф.11 (2007) / Инвентарный номер: 51051 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: М 67 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-44